Abdominal Adiposity Correlates with Adenotonsillectomy Outcome in Obese Adolescents with Severe Obstructive Sleep Apnea - Gustavo Nino; Maria J. Gutierrez; Anjani Ravindra; Cesar L. Nino; Carlos E. Rodriguez-Martinez (Pulmonary Medicine)
Background. Obese adolescents with Obstructive Sleep Apnea (OSA) have a unique pathophysiology that combines adenotonsillar hypertrophy and increased visceral fat distribution. We hypothesized that in this population waist circumference (WC), as a clinical marker of abdominal fat distribution, correlates with the likelihood of response to AT. Methods. We conducted a retrospective cohort study of obese adolescents ( percentile) that underwent AT for therapy of severe OSA (). We contrasted WC and covariates in a group of subjects that had complete resolution of severe OSA after AT () with those obtained in subjects with residual OSA after AT (). Multivariate linear and logistic models were built to control possible confounders. Results. WC correlated negatively with a positive AT response in young adolescents and the percentage of improvement in obstructive apnea-hypopnea index (OAHI) after AT (). Extended multivariate analysis demonstrated that the link between WC and AT response was independent of demographic variables, OSA severity, clinical upper airway assessment, obesity severity (BMI), and neck circumference (NC). Conclusion. The results suggest that in obese adolescents, abdominal fat distribution determined by WC may be a useful clinical predictor for residual OSA after AT.